Contemporary theatre, film and television. Volume 118 a biographical guide featuring performers, directors, writers, producers, designers, managers, choreographers, technicians, composers, executives, dancers, and critics in the United States, Canada, Great Britain and the world - Riggs, Thomas 1963-; Gale Group (Detroit, Mich. Gale, 2012)
Biographical reference providing information on individuals active in the theatre, film, and television industries. Covers not only performers, directors, writers, and producers, but also behind-the-scenes specialists such as designers, managers, choreographers, technicians, composers, executives, dancers, and critics from the United States, Canada, Great Britain, and the world.
Electronic reproduction.
Keywords: Performing arts -- Biography; Performing arts -- United States -- Biography; Performing arts -- Great Britain -- Biography; Performing arts -- Canada -- Biography; Theater -- Biography; Television -- Biography; Motion picture industry -- Biography; Entertainers -- Biography; Actors -- Biography; Motion picture producers and directors -- Biography; Theatrical producers and directors -- Biography; Television producers and directors -- Biography; Dramatists -- Biography; Screenwriters -- Biography; Television writers -- Biography; Designers -- Biography; Theatrical managers -- Biography; Executives -- Biography; Choreographers -- Biography; Composers -- Biography; Dancers -- Biography; Critics -- Biography; Electronic books